Pengaruh Motivasi Intrinsik, Dimediasi Iklim Organisasi terhadap Kinerja Siswa - Elga Badar Ramadhan; Tyna Yunita; Jumawan Jumawan (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to analyze the influence of intrinsic motivation on student performance mediated by the organizational climate at SMAN 4 Tambun Selatan. The type of research used in this research is a quantitative descriptive method. Data collection techniques in literature and the field use questionnaires distributed to students of SMAN 04 Tambun Selatan. Hypothesis testing uses full model Structural Equation Modeling (SEM) analysis with smartPLS. The results obtained by the Intrinsic Motivation Variable (X) x Organizational Climate (Z) x Student Performance (Y) show that the p-values ​​are 0.00 < 0.05, so there is a significant positive influence between the intrinsic motivation variable on student performance which is mediated by the organizational climate at SMAN 04 Tambun Selatan. In conclusion, there is a significant positive influence between intrinsic motivation variables on student performance which is mediated by organizational climate at SMAN 04 Tambun Selatan. Suggestions, schools can develop student motivation programs, improve organizational climate, or other efforts aimed at improving student performance. Keywords: Organizational Climate, Student Performance, Intrinsic Motivation.